Aspirin and heparin in the treatment of recurrent spontaneous abortion associated with antiphospholipid antibody syndrome: A systematic review and meta-analysis - Yu, Xiaomei (Exp Ther Med, 2021)
The present study aimed to review relevant, randomized, controlled trials in order to determine the effects of aspirin and heparin treatment on recurrent spontaneous abortion (RSA) in women with antiphospholipid syndrome (APS). Previous relevant studies were identified using PubMed, Cochrane, Embase, CNKI, VANFUN and VIP by retrieving appropriate key words. Additionally, key relevant sources in the literature were reviewed and articles published before May 2019 were included. The 22 selected studies included 1,515 patients in the treatment group and 1,531 patients in the control group. These previous studies showed that heparin and aspirin significantly improved live birth rate when compared with treatments using intravenous immunoglobulin, aspirin alone or aspirin combined with prednisone. Moreover, heparin and aspirin greatly increased the birth weight compared with placebo and improved vaginal delivery relative to intravenous immunoglobulin. The gestational age at birth was significantly higher in the heparin and aspirin group compared with the placebo group and the incidence of intrauterine growth restriction was lower in the heparin and aspirin group compared with the placebo group. Furthermore, heparin and aspirin markedly reduced the incidence of miscarriage compared with the aspirin group and the placebo group, and the incidence of pre-eclampsia was lower in the heparin and aspirin group than the placebo group. Thus, heparin and aspirin could be further examined for the treatment of RSA in women with APS.